The private museum of John Septimus Roe, dispersed in 1842. Issue 1 (April 2020) - Fishburn, Matthew
Abstract : In 2009, the State Library of New South Wales acquired a collection of 201 letters written by the Royal Navy officer John Septimus Roe. Dating between 1807 and 1829, these letters cover Roe's time serving with Phillip Parker King on the Australian coastal survey voyages of the Mermaid and Bathurst (1817–1823), and later with James Bremer on the Tamar on the Australian north coast and in Southeast Asian waters (1824–1827). This article, based on a close study of the letters, explores how Roe's interest in natural history and ethnography developed during this time, leading to the establishment of an extensive private museum, with the particular encouragement of his brother William Roe, at the family home, the rectory of the church of St Nicolas, Newbury, Berkshire. Roe took advantage of his time, while surveying areas of Australia largely unknown to Europeans, to make a collection of some scientific importance, but the museum was sold and dispersed in 1842, so that the close reading of the letters provides the only substantive account of its contents. The letters also provide an opportunity to make a case study of the web of connections – and opportunities for promotion – that collecting provided for a then quite junior British naval officer. Although no item with a confirmed provenance to the museum is recorded, it is hoped that this article may provide clues that will lead to the unearthing of specimens acquired by Roe which formed part of his enormous natural history collection, and also to the Aboriginal spears, weapons and other implements collected from the remoter stretches of the Australian coast.